STUDI PEMANFAATAN CANGKANG KERANG KAPAH (Meretrix sp.) SEBAGAI FILTER AIR TANAH DI KOTA TARAKAN - Ronaldo Medi Bottong; Ratno Achyani; Dori Rachmawani (Jurnal Borneo Saintek, 2022)
Tarakan City has the groundwater potency for clean water needs, However, for its use, it needs to treat it first in order to quality standards, through filtration technology by using the waste of Asiatic hard clam sheel (Meretrix sp.). the purpose of this study was to determine the effectiveness of using Asiatic hard clam sheel as the groundwater filters in Tarakan City. The research method used in this study was an experimental method with a complete randomized design (RAL) with three treatments. The material used was Asiatic hard clam shell with a filter level of 30, 60 and 100 Cm with a combination of the use of activated charcoal, quartz sand and gravel to determine the best composition. The parameters tested were according to the regulation of the Minister of Health No.32 of 2017 (Water Qualitiy Standards for Sanitary Hygiene Needs) namely turbidity, color, odor, pH, temperature, TDS, TSS, nitrates, nitrites, Fe and manganese (Mn). The results showed that the efeectiveness of the filter for each parameter was different. For the effective manganese parameters at a filter level of 30 cm, which was 36 %, pH, TDS, and Effective color at the level of 60 cm with successive valus of 61, 42 and 17 %. The parameters of nitrite, nitrate, TSS and effective turbidity at the filter level of 100 cm were 95, 97, 84 and 76%. Thes use of Asiatic hard clam shell as a groundwater filter was effective in improving the quality of raw water physically and meeting the requirements according to the quality standards used.